Teologi Islam Moderat Berbasis Intellectual Humility Kiai Sholeh Bahruddin: Perspektif Psikologi Positif - Achmad Muhibin Zuhri (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
This study explores moderate Islamic theology with a focus on applying the concept of intellectual humility by Kiai Haji Sholeh Bahruddin. Intellectual humility is a humble attitude that acknowledges human knowledge's limitations. The purpose of this study is to explore how the principle of intellectual humility can influence Kiai Haji Sholeh Bahruddin's view of religion and society, as well as its positive impact from a positive psychology perspective. The research method used is a qualitative approach with a phenomenological approach. Data were obtained through in-depth interviews with Kiai Haji Sholeh Bahruddin, as well as analysis of documents related to his views on moderate Islamic theology. Data analysis was carried out in the following steps: first, identifying the beliefs and values of moderate Islamic theology as applied by Kiai Haji Sholeh Bahruddin; second, describing how intellectual humility is reflected in the approach and views of Kiai Haji Sholeh Bahruddin; third, analyze the positive impact of the application of intellectual humility in forming an inter-religious dialogue, tolerance, and harmonious relations in society. The results of this study reveal that Kiai Haji Sholeh Bahruddin applies intellectual humility in his interpretation and communication of Islamic teachings, which opens up space for more open interreligious dialogue and acceptance of different views. This research aims to support the importance of a moderate approach to religion and show that intellectual humility can be an important instrument in building an inclusive and harmonious society.